The influence of Platelet-rich fibrin on the inflammatory response, bone metabolism and cell differentiation ability of Temporomandibular joint osteoarthritis - Zhao, Yuhan; Dai, Hongwei (Journal of Medical Biochemistry, 2025)
Objective: This study aims to explore the regulatory effects of platelet-rich fibrin (PRF) on serum inflammatory response, bone metabolic balance and cell differentiation ability in patients with temporomandibular joint osteoarthritis (TMJ-OA) at the molecular levels.Methods: Sixty patients randomly divided into Group A and Group B (30 cases in each group). Group A was treated with meloxicam dispersible combined with hydroxychloroquine sulfate (HCQ); Group B was supplemented with autologous PRF intra-articular injection on the basis of Group A. Fasting venous blood was collected before treatment and 3 months after treatment. Inflammatory and bone metabolism markers such as IL-1β, IL-6, TNF-α, OPN, ALP, and Runx2 were detected by ELISA, and coagulation indicators such as APTT and PT were determined by an automatic coagulation analyzer.Results: After treatment, the inflammatory factors (IL-1β, IL-6, TNF-α) in both groups decreased significantly, but the decrease in group B was more significant (P
Keywords: Temporomandibular joint osteoarthritis; Platelet-rich fibrin; Inflammatory factors; Cell differentiation; Coagulation function; Bone metabolism